Understanding Research Motivations and Barriers Among Danish Sonographers in Radiology Departments: A Qualitative Study - Brage, Karen; Holm, Susanne; Mørup, Svea Deppe; Pedersen, Malene Roland Vils (Radiography Open, 2025)
Introduction: In Denmark sonographers, undergo profound training and have a notable presence in clinical practice. Understanding the factors behind their limited research engagement is important. This study aimed to examine the factors influencing sonographers' research involvement, focusing on motivational elements and barriers. Our investigation was structured around three key research questions: a) What motivates sonographers to engage in research? b) What obstacles hinder their involvement? c) How can we enhance the participation of sonographers in research in Denmark? Methods: This study had an explorative inductive qualitative approach. The data collection method was a focus group session with sonographers from the National Sonographers Network. The focus group session followed a structured guide and was verbatim transcribed. Thematic analysis by coding and identifying themes was performed individually by three authors. Subsequently, Social Cognitive Theory was incorporated as a framework for further analysis. Results: Regarding motivations for engaging in research, the themes were Impact on Practice and Personal Interest. In terms of obstacles to research involvement, the themes included Challenges in Staffing and Time Management, Low Priority and Interest, Limited Research Experience and Practical Skills, and Insufficient Support. Regarding enhancements for participation, the themes were Management and Communications and Networks. Conclusion: Sonographers in Danish public radiology departments demonstrate a high interest in research, driven by personal and clinical practice impacts. Their intrinsic motivation fosters idea generation and collaboration in research. Key barriers include heavy workloads and limited research skills. Cultivating a supportive, research-friendly environment is important for meaningful participation. Enhancing management and colleague support can bridge existing gaps and encourage active research engagement.